Patterns of Population Structure Vary Across the Range of the White Sturgeon. Issue 5 (9th August 2013) - Schreier, A. Drauch; Mahardja, B.; May, B.
Abstract: Critical unknowns surrounding the basic biology of White Sturgeon Acipenser transmontanus have hindered management and conservation efforts. Population genetic data may be used to address some of these uncertainties, but previous examinations of population structure in White Sturgeon have been limited by the highly duplicated nature of the species' genome. We report results from an analysis of White Sturgeon population structure within and among drainages using 13 polysomic microsatellite loci. Genetic diversity levels varied widely among regions, and the lowest levels were observed in the endangered Kootenai River Distinct Population Segment and the highest levels were detected in regions with access to estuarine and marine habitat. Patterns of within‐drainage population structure varied, and no structure was detected in the Sacramento–San Joaquin drainage and a complex pattern of isolation by distance was revealed in the Columbia–Snake River drainage. These results contrast a previously published evaluation of a White Sturgeon population structure in the Fraser River, which revealed several genetically distinct populations within a single drainage. Examination of population structure among drainages, including from samples collected across the species range, revealed six populations. Populations in the Sacramento–San Joaquin, Kootenai, lower Fraser, and upper Fraser River drainages were distinct. The complex isolation‐by‐distance pattern discovered in the within‐drainage analysis of the Columbia–Snake River drainage was supported by the among‐drainage population structure analysis. Our results provide little support for the practice of managing each impounded reach of the Columbia–Snake River system as a genetically distinct population as adjacent reaches show little to no genetic divergence in these analyses. Variation in patterns of population structure across the species range indicates that the scale of spawning site fidelity for White Sturgeon varies regionally, which has implications for recruitment failure mitigation.